THE ROLE OF CHLOROQUINE AND PSYCHOSOCIAL SUPPORT IN A PATIENT WITH COVID-19: A CASE REPORT IN INDONESIA - Ade Dilaruri; Ira Rahmawati (Belitung Nursing Journal, 2020)
Background: COVID-19 is caused by the 2019 novel coronavirus (2019nCoV) which was identified on 7 January 2020 by the Chinese Center for Disease Control and Prevention (CDC) from the throat swab sample of a patient. This novel coronavirus is phylogenetically similar to the severe acute respiratory syndrome coronavirus (SARS-CoV) that caused SARS outbreak in 2002. Objective: To describe a case of a COVID -19 patient in a hospital in Indonesia. Case Report: A 55-year-old male was admitted to the Emergency Department of Arifin Achmad Hospital on 31 March 2020. He was transferred from a private hospital after three days of hospitalization. Previously, he came to another hospital complaining palpitation, cough, having difficulty of breathing, and intermittent fever. He then was advised to be admitted and tested for a COVID-19 test. At first, he did not admit to having traveled recently. After three days, the pharyngeal swab test was received confirming that he was contracted with COVID-19. The patient was then transferred to our hospital and hospitalized for ten days. Discussion: The patient was fully recovered after ten days of treatment with antiviral drug namely Oseltamivir 75 mg orally twice a day and chloroquine phosphate 500 mg twice a day orally. The combination of both drugs showed an immune-modulating activity which might increase its antiviral effects. Therefore, the use of this agent in COVID-19 patients might be worthwhile. During hospitalization, reducing patient anxiety was also one of our main goals as many studies has found that anxiety is associated with poor immune system. Conclusion: This case report demonstrated the current situation in Indonesia where people become reluctant to fully disclose their symptoms or travel history to the health care workers, which may put many others on the risk of being transmitted with the virus. Although the proven efficacy of chloroquine is still lacking, it has become the favorable choice at this moment as indicated in our study. Reducing the patient’s anxiety towards the disease may help to speed the patient’s recovery. Also, we need to educate public that COVID-19 might be a life-threatening disease but it is also a treatable disease.